Aerobic oxidation and oxidative esterification of alcohols through cooperative catalysis under metal-free conditions. Issue 71 (16th August 2021) - Karimi, Babak; Ghahremani, Mina; Vali, Hojatollah; Ciriminna, Rosaria; Pagliaro, Mario
Abstract : The ABNO@PMO-IL-Br material obtained by anchoring 9-azabicyclo[3.3.1]nonane-3-one N -oxyl within the mesopores of PMO with bridged imidazolium groups is a robust bifunctional catalyst for the metal-free aerobic oxidation of a wide variety of alcohols under oxygen balloon reaction conditions. Abstract : The ABNO@PMO-IL-Br material obtained by anchoring 9-azabicyclo[3.3.1]nonane-3-one N -oxyl (keto-ABNO) within the mesopores of periodic mesoporous organosilica with bridged imidazolium groups is a robust bifunctional catalyst for the metal-free aerobic oxidation of numerous primary and secondary alcohols under oxygen balloon reaction conditions. The catalyst, furthermore, can be successfully employed in the first metal-free self-esterification of primary aliphatic alcohols affording valued esters.